2015
DOI: 10.1021/acs.iecr.5b00453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optimization of the Flow Rate Distribution in Heat Exchanger Networks for Fouling Mitigation

Abstract: Heat exchanger networks are structures composed of a set of heat exchangers interconnected in order to reduce utilities consumption. During the network operation, heat exchangers may present a decrease of their thermal effectiveness caused by fouling, which corresponds to the undesirable accumulation of deposits over their thermal surface. In this context, this paper presents a proposal to increase the energy recovered in heat exchanger networks affected by fouling through the optimization of the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…The relation between fouling rate and the thermofluid dynamic conditions can be explored not only in the design phase, as presented in the current article, but also in the analysis of the operation of the exchanger. 47,48 2. The hydraulic impact of fouling can increase the pressure drop due to the reduction of the free flow area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between fouling rate and the thermofluid dynamic conditions can be explored not only in the design phase, as presented in the current article, but also in the analysis of the operation of the exchanger. 47,48 2. The hydraulic impact of fouling can increase the pressure drop due to the reduction of the free flow area.…”
Section: Resultsmentioning
confidence: 99%
“…The examples where the performance of the proposed approach was tested in comparison of alternative solutions involving the fouling modeling that ignores the hydraulic impact and fixed fouling resistances showed that:The inclusion of the fouling modeling in the design can identify solutions with a considerable reduction of the heat transfer area because allows the optimization procedure to identify heat exchanger alternatives that mitigate the fouling problem (e.g., solutions in the no fouling region). The relation between fouling rate and the thermofluid dynamic conditions can be explored not only in the design phase, as presented in the current article, but also in the analysis of the operation of the exchanger 47,48 The hydraulic impact of fouling can increase the pressure drop due to the reduction of the free flow area.…”
Section: Discussionmentioning
confidence: 99%
“…Operationally, a practical alternative for fouling mitigation is to manipulate the flow rate distribution in the network over time, through use of by-passes of individual units and control of flow split between parallel branches in the HEN. Optimising such flow distribution profiles has also been formulated as a mathematical programming problem with the objective to minimize the operational cost 12 .…”
Section: Introductionmentioning
confidence: 99%
“…1,13,14 . On the other hand, some works tackle the second problem only from a dynamic optimization perspective ignoring the cleaning scheduling 12,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation